Waqf Accounting Practices Based on PSAK 112 at the Millennial Waqf Institution in Bogor - Andri Soemitra; Alfi Amalia; Hastuti Olivia; Lukman Hamdani; Isra Hayati (Lan Tabur: JURNAL EKONOMI SYARIAH, 2026)
Introduction: The implementation of PSAK 112 concerning waqf accounting in waqf institutions in Indonesia still faces various challenges, particularly related to limited understanding and inadequate technological infrastructure. This study aims to evaluate the implementation of PSAK 112 at the Millennial Waqf Institution in Bogor City, focusing on organizational readiness and the obstacles encountered during the implementation process. Methods: The research employs a qualitative method, with data collected through in-depth interviews and observations at several waqf institutions. Results: The findings indicate that although the Millennial Waqf Institution in Bogor City has succeeded in implementing PSAK 112, it still encounters difficulties, especially in terms of understanding the standards and limitations of technological infrastructure. These findings suggest that increased training and strengthened infrastructure are necessary to support broader and more effective implementation. Conclusion and suggestion: The implication of this study highlights the importance of a more inclusive and comprehensive strategy in implementing PSAK 112, which not only enhances transparency and accountability but also strengthens public trust in the management of waqf in Indonesia.